AL JAM’IYATUL WASHLIYAH AS AN EDUCATIONAL INSTITUTION IN THE NORTH SUMATRA PROVINCE (Their History, Ideology, Educational Typology, and Problems) - Nisa, Khairun; Harahap, Nasruddin (JURNAL TARBIYAH, 2023)
Al-Jam'iyatul Al Washliyah is an Islamic educational institution in Indonesia that was founded in 1952 in Medan, North Sumatra. This institution was founded by Haji Mohd Arsyad Al Banjari to spread Islamic teachings and strengthen Muslim identity in Indonesia. Al-Jam'iyatul Al Washliyah has several branches in various regions in Indonesia. Through field study with phenomenological research, Al Washliyah was founded during the Dutch colonial period to unite Muslims and fight for Indonesian independence. They have a high commitment to education, establishing schools, and madrasas, and forming the Education, Teaching and Culture Council. This research will focus on the dynamics of the Al-Washliyah educational institution in the past, present, and future so that it can show the results of intellectual exploration among Islamic scholars (Ulama) and intellectuals regarding the dynamics of Islamic education in the classical and contemporary periods in Indonesia. This research is limited to the development of the Al Jam’iyatul Washliyah Educational Institution in North Sumatra, from 2016 to 2022 in 3 Districts/Cities and history by focusing on their Ideology, Educational Typology, and Problems.